Do Associations Support Authoritarian Rule? Tentative Answers from Algeria, Mozambique, and Vietnam - Jörg Wischermann; Bettina Bunk; Patrick Köllner; Jasmin Lorch (German Institute of Global and Area Studies (GIGA), 2016)
Whether associations help to democratise authoritarian rule or support those in power is a contested issue that so far lacks a cross-regional perspective. Drawing on relational sociology, this paper explores the impact of state power in Algeria, Mozambique, and Vietnam on associations and vice versa. We focus on decision-making in associations and on three policy areas - welfare policy concerning HIV/AIDS, economic policy concerning small and mediumsized enterprises, policies concerning gender equality and the rights of women and sexual minorities - to assess the relations between associations and the state's infrastructural and discursive power. Most associations interviewed by us in the three countries accept or do not openly reject the state's and/or the state ruling party's various forms of interference in internal decision-making processes. Whereas associations in Algeria and Vietnam help to maintain the state's control through welfare provision, associations in Mozambique can weaken this form of infrastructural state power. Moreover, business and professionals' associations in all three countries help maintain the state's control through limited participation, i.e. another form of infrastructural state power. Finally, associations in all three countries support the state's discourse and policies in the area of gender equality and women's rights, though in all three countries at least some NGOs help weaken this form of state power.
Keywords: 300; civil society; associations; state; Algeria; Mozambique; Vietnam